2006
DOI: 10.1529/biophysj.105.073114
|View full text |Cite
|
Sign up to set email alerts
|

Matrices with Compliance Comparable to that of Brain Tissue Select Neuronal over Glial Growth in Mixed Cortical Cultures

Abstract: Cortical neurons and astrocytes respond strongly to changes in matrix rigidity when cultured on flexible substrates. In this study, existing polyacrylamide gel polymerization methods were modified into a novel method for making substrates capable of engaging specific cell-adhesion receptors. Embryonic cortical dissociations were cultured on polyacrylamide or fibrin gel scaffolds of varying compliance. On soft gels, astrocytes do not spread and have disorganized F-actin compared to the cytoskeletons of astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

45
645
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 662 publications
(696 citation statements)
references
References 27 publications
45
645
6
Order By: Relevance
“…. Although this value is much lower than any bulk values, this rigidity remains in a range known to have no effect on cortical neuron development 25 . Therefore, even by considering the extreme situation where the nano-pillars might display a linear elastic behavior in a large range of deformations, the changes we observed in neuronal elongation do probably not result from the flexibility of nano-pillars.…”
Section: -About the Development Of Neurites On Nano-pillarsmentioning
confidence: 75%
“…. Although this value is much lower than any bulk values, this rigidity remains in a range known to have no effect on cortical neuron development 25 . Therefore, even by considering the extreme situation where the nano-pillars might display a linear elastic behavior in a large range of deformations, the changes we observed in neuronal elongation do probably not result from the flexibility of nano-pillars.…”
Section: -About the Development Of Neurites On Nano-pillarsmentioning
confidence: 75%
“…During the normal wound healing process, it is very common for the ECM of damaged tissues to be replaced by fibrous tissue that is stiffer than the original ECM. 57 The newly formed tissue of increased stiffness is generally referred to as scar tissue. Matrix stiffening in scar tissue tends to be the product of abnormal and/or increased ECM deposition, increased ECM crosslinking, and reduced or abnormal matrix degradation.…”
Section: Cellular Response To Ecm Stiffness During Tissue Homeostasismentioning
confidence: 99%
“…Several recent studies have shown that soft substrates stimulated neurite extension and branching, but inhibited glial cell growth (Balgude et al, 2001;Engler et al, 2004;Flanagan et al, 2002;Georges et al, 2006;Lamoureux et al, 2002;Strassman et al, 1973). However, mechanisms of this regulation are not clear.…”
Section: Introductionmentioning
confidence: 99%